2018
DOI: 10.1016/j.gfs.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of systems models to identify food waste drivers

Abstract: In developed countries, the largest share of food waste is produced at household level. Most studies on consumers' food waste use models that identify covariates as significant when in fact they may not be, particularly where these models use many variables. Here, using EUlevel Eurobarometer data from 2013, we use alternative analytical methods that avoid these problems (Bayesian Networks) to identify the impact of household characteristics and other variables on self-assessed food waste. Our analysis confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Understanding why age and country-level differences occur may be of paramount importance for designing better food waste policy interventions, and needs further research via multiple methods. Nevertheless, the probabilistic understanding of the drivers of food waste that have been showcased in Grainger, M. J. et al (2018aGrainger, M. J. et al ( , 2018bGrainger, M. J. et al ( , 2018d allows future action and research.…”
Section: Applications and Preliminary Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding why age and country-level differences occur may be of paramount importance for designing better food waste policy interventions, and needs further research via multiple methods. Nevertheless, the probabilistic understanding of the drivers of food waste that have been showcased in Grainger, M. J. et al (2018aGrainger, M. J. et al ( , 2018bGrainger, M. J. et al ( , 2018d allows future action and research.…”
Section: Applications and Preliminary Resultsmentioning
confidence: 99%
“…The use of systems models to identify food waste drivers - Grainger, M. J. et al (2018a) This paper investigated the drivers of household food waste using Bayesian Networks to identify the impact of household characteristics and other variables on self-assessed food waste. Using EU-level Eurobarometer data from 2013, the study confirmed that the country, the age of the respondent, the status (student/non-student), and a belief that the family wastes too much are related to the level of self-assessed food waste.…”
Section: Machine Learning and Bayesian Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have detected geographical differences in the individual behaviours towards food waste among EU countries, due to factors such as per-capita income, and citizens’ perception of sustainability issues [ 7 , 9 11 ]. Although developed countries present high per-capita incomes, hunger in these countries is a reality: e.g., approximately 4% of US households, and more than 5% of Australian households are experiencing hunger [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates of food loss and waste generation range between 194-389 kg per person per year at the global scale, and between 158-298 kg per person per year at European level (Corrado and Sala, 2018), which translates into 88 million tons of food annually wasted, or equivalent losses of around 143 billion Euro (FUSIONS, 2016). Since the European Union (EU) is globally the second most significant contributor in terms of per capita food losses and waste at consumption and pre-consumption stages (FAO, 2019), it is unsurprising that debates on food waste management are thus becoming increasingly vocal amongst European stakeholders at national and local level (Gustavsson et al, 2011;Priefer et al, 2016;Grainger et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%